Spoken Word Recognition Using Slantlet Transform and Dynamic Time Warping - Sadiq J. Abou-Loukh; Samah Mutasher Gatea (مجلة النهرين للعلوم الهندسية, 2011)
Speech recognition system has been widely used by many researchers using different methods to fulfill a fast and accurate system. Speech signal recognition is a typical classification problem, which generally includes two main parts: feature extraction and classification. In this work, three feature extraction methods, namely SLT, DWT Db1 and DWT Db4, were compared. The dynamic time warping (DTW) algorithm is used for recognition. Twenty three Arabic words were